Pengembangan Bahan Ajar pada Matakuliah Statistik Infrensial Berbasis Bimbingan dan Konseling - Muh. Mansyur Thalib; Abd. Munir; Hasan Hasan (Kuras Institute, 2022)
The purpose of this study was to produce teaching materials for infrensial statistics in the Guidance and Counseling study program. The collection of teaching material assessment data from experts uses a closed (direct) questionnaire, while student response data uses a questionnaire through the